2017
DOI: 10.1515/math-2017-0122
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of forests

Abstract: An edge-magic total labeling of an .n; m/-graph G D .V; E/ is a one to one map from V .G/ [ E.G/ onto the integers f1; 2; : : : ; n C mg with the property that there exists an integer constant c such that .x/ C .y/ C .xy/ D c for any xy 2 E.G/. It is called super edge-magic total labeling if .V .G// D f1; 2; : : : ; ng. Furthermore, if G has no super edge-magic total labeling, then the minimum number of vertices added to G to have a super edgemagic total labeling, called super edge-magic deficiency of a graph … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Lee and Shah [6] proved this conjecture for trees with upto 17 vertices by the help of a computer. Javed et al [7] provided the SEMT labeling for the 2-sided generalized comb. In [4] Enomoto et al showed that all caterpillars possess SEMT labeling.…”
Section: Basic Terminologies and Preliminary Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee and Shah [6] proved this conjecture for trees with upto 17 vertices by the help of a computer. Javed et al [7] provided the SEMT labeling for the 2-sided generalized comb. In [4] Enomoto et al showed that all caterpillars possess SEMT labeling.…”
Section: Basic Terminologies and Preliminary Resultsmentioning
confidence: 99%
“…Two-sided generalized comb denoted by Cb ν,υ is de ned in [7] and have proved that it admits SEMT labeling.…”
Section: Resultsmentioning
confidence: 99%